THE SYNERGY OF OPTIMIZING PROJECT MANAGEMENT PRACTICES FOR QUALITY MANAGEMENT IN RESIDENTIAL BUILDINGS - Imadeddine Reghiss; Riad Abadli (International Journal of Innovative Technologies in Social Science, 2024)
This paper provides a bibliometric study based on data from Scopus and the VOS Viewer program to investigate the relationship between optimization strategies, project management, and quality management in the context of residential constructions. With an emphasis on a number of factors, including publishing nations, years, fields, authors, citations, and keywords, the analysis encompasses 85 articles from 1995 to 2023. The main conclusions show that the top four nations in terms of the number of publications on this subject are China, the US, Australia, and Canada. The research reveals noteworthy patterns in the disciplines that have made contributions to this topic, suggesting that optimization in construction and management techniques is studied from a multidisciplinary perspective. In order to improve the performance of residential building projects, the paper highlights the growing significance of combining optimization techniques with efficient project management and quality assurance. Additionally, it lists key works and prominent writers who have influenced the conversation in this field. All things considered, this bibliometric study offers insightful information to scholars and professionals who are interested in the nexus of these important fields, indicating that interdisciplinary cooperation might result in better residential building project outcomes.